Manajemen Pemebelajaran Anak Berkebutuhan Khusus Pada Era PTM Terbatas di SD Negeri Inklusi Oku Timur - Ratih Purnama Pertiwi; Sri Enggar Kencana Dewi; Rubia A. Abdulwahab (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The background of this research is the learning management process carried out during the limited Face-to-Face Learning (PTM) era at SD Negeri OKU Timur Inclusion. This study aims to identify and evaluate the planning and implementation of learning for children with special needs in the limited PTM era at SD Negeri Inclusion OKU Timur. Data collection techniques used are observation, interviews, and documentation. Interviews were conducted with 2 (two) school principals and 2 (two) teaching staff. Test the validity of the data used, namely by using the source triangulation technique. The results of this study indicate that children with special needs in inclusive primary schools, which are driving schools, can carry out joint learning activities with children who do not have special needs well, and in learning, teachers in inclusive primary schools also provide learning facilities or learning media for students with special needs. The students who have special needs and students who do not have special needs are also very close; there are no negative things such as bullying or anything else. The learning process uses planning that still uses the Offline Learning Implementation Plan, and the curriculum is adapted to the curriculum used in regular classes, which are used as inclusive classes. The implementation of learning in the limited PTM era continued to carry out learning as usual, but the implementation time was adjusted to the time that the school had made; children with special needs had the morning shift from 07.00 to 10.00. while for other regular classes from 07.00 to 12.45. the evaluation process carried out in learning for children with special needs is different from regular students. The KKM used is also different. If the KKM of regular students reaches a score of 70-85, the KKM of students with special needs is between 50-65. 2 sub-themes; apart from that, PTS is held in the middle of the semester, and PAS is held at the end of the semester. The assessment of students with special needs is adjusted to the abilities of the students.